Extinction of all infectious HIV in cell culture by the CRISPR-Cas12a system with only a single crRNA. Issue 10 (13th April 2020) - Gao, Zongliang; Fan, Minghui; Das, Atze T; Herrera-Carrillo, Elena; Berkhout, Ben
Abstract: The CRISPR-Cas9 system has been used for genome editing of various organisms. We reported inhibition of the human immunodeficiency virus (HIV) in cell culture infections with a single guide RNA (gRNA) and subsequent viral escape, but complete inactivation of infectious HIV with certain combinations of two gRNAs. The new RNA-guided endonuclease system CRISPR-Cas12a (formerly Cpf1) may provide a more promising tool for genome engineering with increased activity and specificity. We compared Cas12a to the original Cas9 system for inactivation of the integrated HIV DNA genome. Superior antiviral activity is reported for Cas12a, which can achieve full HIV inactivation with only a single gRNA (called crRNA). We propose that the different architecture of Cas9 versus Cas12a endonuclease explains this effect. We also disclose that DNA cleavage by the Cas12a endonuclease and subsequent DNA repair causes mutations with a sequence profile that is distinct from that of Cas9. Both CRISPR systems can induce the typical small deletions around the site of DNA cleavage and subsequent repair, but Cas12a does not induce the pure DNA insertions that are routinely observed for Cas9. Although these typical signatures are apparent in many literature studies, this is the first report that documents these striking differences.